2010
DOI: 10.1093/bja/aep363
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-induced hyperalgesia in a mice model of orthopaedic pain: preventive effect of ketamine

Abstract: Background. The aim of this study was to assess the preventative effect of ketamine on the exaggerated postoperative pain observed in sufentanil-treated mice and its ability to improve the analgesic effectiveness of morphine during the postoperative period in an orthopaedic model of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Although ketamine acts on a variety of receptors, its analgesic effects stem mainly from its antagonism of NMDARs and prevention of central sensitization (Hirota and Lambert, 1996). One study has demonstrated the efficacy of NMDAR antagonists for preventing OIH (Minville et al, 2010). Furthermore, a number of investigations found that clinical doses of naloxone antagonize opioid effects, whereas ultra-low doses enhance the antinociceptive effects of morphine (Tsai et al, 2008;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although ketamine acts on a variety of receptors, its analgesic effects stem mainly from its antagonism of NMDARs and prevention of central sensitization (Hirota and Lambert, 1996). One study has demonstrated the efficacy of NMDAR antagonists for preventing OIH (Minville et al, 2010). Furthermore, a number of investigations found that clinical doses of naloxone antagonize opioid effects, whereas ultra-low doses enhance the antinociceptive effects of morphine (Tsai et al, 2008;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[73][74][75] Alternatively, it has been speculated that biologically active glucuronide metabolites may play a role in morphine-induced hyperalgesia. 76,77 The metabolite morphine-3-glucuronide, which is known to possess very little affinity for any of the opioid receptor subtypes, 78,79 is able to stimulate potent neuro-excitatory effects on behaviour when administered to rodents, 80, 81 yet this hypothesis does not explain opioid-induced hyperalgesia following administration of opioids which do not form glucuronide metabolites such as fentanyl.…”
Section: Possible Mechanisms Of Opioid-induced Hyperalgesiamentioning
confidence: 99%
“…Patient tolerability to IV clarithromycin is poor [2][3][4]; indeed one study group was forced to discontinue IV infusions in 50% of its participants due to drug-induced severe pain [2]. Most studies investigating IV macrolide tolerance and subsequent irritation have been shown in patients treated for lower respiratory tract infections [3,4].…”
Section: Intravenous Macrolide Use: a Reminder Of The Dangers Of Rapimentioning
confidence: 99%
“…Additional benefits include improved staff scheduling, medical decision-making support, and quality improvement monitoring [2]. Advances in the sophistication of computer workstations and network components, and an industry trend towards electronic medical record (EMR) implementation, have driven the development of AIMS that interfaces with the hospital's software system.…”
Section: Discounted Cash Flow Of Anesthesia Information Management Symentioning
confidence: 99%
See 1 more Smart Citation